2019
DOI: 10.1016/j.eclinm.2019.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparing outcomes following total neoadjuvant therapy and following neoadjuvant chemoradiation therapy in patients with locally advanced rectal cancer

Abstract: BackgroundThere is recent interest in treating locally advanced rectal cancer (LARC) patients with total neoadjuvant therapy (TNT). However, whether TNT is associated with improved overall survival (OS) remains unknown. This study compares outcomes following TNT and following neoadjuvant chemoradiation therapy (nCRT) in patients with LARC, clinically defined cT3/4 or node positive disease, using the National Cancer Database.MethodsLARC patients diagnosed between 2004–2015 were included. TNT was defined as mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 16 publications
3
15
0
Order By: Relevance
“…No statistically significant difference was observed in five-year OS between treatment groups (TNT 76.2% vs. nCRT 69.9%), despite higher utilization of TNT for more advanced-stage disease. This is consistent with other NCDB analyses demonstrating no difference in overall survival between treatment groups [13,14]. However, when stratified by clinical stage, we found that patients with cT3 or cN1 disease had better OS when treated with TNT versus nCRT.…”
Section: Discussionsupporting
confidence: 92%
“…No statistically significant difference was observed in five-year OS between treatment groups (TNT 76.2% vs. nCRT 69.9%), despite higher utilization of TNT for more advanced-stage disease. This is consistent with other NCDB analyses demonstrating no difference in overall survival between treatment groups [13,14]. However, when stratified by clinical stage, we found that patients with cT3 or cN1 disease had better OS when treated with TNT versus nCRT.…”
Section: Discussionsupporting
confidence: 92%
“… 27 29 The NCDB does not delineate TNT in the database, and using the definition as described by Zhu et al, our study contains only 49 (2.0%) patients that may have undergone TNT. 13 Due to the low percentage and need for a surrogate definition, these patients were not removed from the cohort.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 TNT was defined as any patient that received radiotherapy and multi-agent chemotherapy prior to oncologic resection, RT was started a minimum of 2 months after chemotherapy, and no adjuvant chemotherapy was given. 13 Cancer-specific and treatment-specific variables were also collected. Hospital volume was determined by calculating the total number of surgical cases in the rectum NCDB PUF for each facility.…”
Section: Methodsmentioning
confidence: 99%
“…TNT is an emerging systemic treatment regimen that incorporates combination chemotherapy into the neoadjuvant therapy 26–28 . It aims to improve rates of pathological complete response and reduce the risk of distant failure, which is the ultimate determinant of OS 28,29 .…”
Section: Discussionmentioning
confidence: 99%